Doped modified porous carbon negative electrode material and preparation method thereof
By performing multiple reaction treatment on sugarcane bagasse, doped modified porous carbon negative electrode material is prepared, which solves the problems of low specific capacity and safety hazards of existing graphite negative electrode materials, and improves the specific capacity and cycle stability of the battery.
Patent Information
- Application Number
- CN202411724921.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-11-28
AI Technical Summary
The theoretical specific capacity of existing graphite negative electrode materials is low and there is a "lithium evolution" phenomenon, which leads to safety hazards and application restrictions, and requires improving the specific capacity and cycle stability of the battery.
By pretreating sugarcane bagasse and multi-step reaction treatment, a doped modified porous carbon negative electrode material was prepared, and phosphorus, nitrogen and iron oxides were introduced into the material to form a porous structure and molecular cage structure to improve the specific surface area and conductivity of the material.
It significantly improves the specific capacity and cycle stability of the battery, improves the electrode dynamics and electrolyte contact characteristics, and enhances the electrochemical performance.
Smart Images

Figure BDA0005158966990000091
Abstract
Description
Technical Field
[0001] The present invention relates to the field of electrode materials, and in particular to a doped and modified porous carbon negative electrode material and a preparation method thereof. Background Art
[0002] With the advancement of science and technology, the requirements for energy storage equipment in fields such as electronic products, electric vehicles, medical equipment, and aerospace are increasing. Among the many energy storage devices, batteries with high energy density, small size, and long cycle life have gradually become a hot topic of research.
[0003] In general, the main types of negative electrode materials studied for batteries include: carbon materials, tin-based materials, silicon-based materials, nitrides, phosphides and transition metal oxides. Considering comprehensive factors such as cycle capacity, specific capacity and production cost, the most ideal negative electrode material is carbon material. The most widely used negative electrode material on the market is still graphite negative electrode material. However, the theoretical specific capacity of graphite negative electrode is only 372mAh / g, and the energy density is low. At the same time, the "lithium precipitation" phenomenon of graphite negative electrode material in lithium-ion battery applications has great safety hazards. These problems greatly limit the application of graphite negative electrode in batteries. Therefore, improving battery specific capacity and cycle stability has become the key to its further development. In order to solve the above problems, it is necessary to modify carbon materials. The current modification methods mainly include heteroatom doping of carbon materials, nanostructured structure design and porous structure design. Summary of the invention
[0004] The purpose of the present invention is to provide a doped modified porous carbon negative electrode material and a preparation method thereof, so as to solve the problems existing in the prior art.
[0005] In order to solve the above technical problems, the present invention provides the following technical solutions:
[0006] A doped and modified porous carbon negative electrode material is characterized in that the doped and modified porous carbon negative electrode material is obtained by mixing modified bagasse and ferrous acetate, then mixing with polydimethylsilane, and drying, calcining, grinding and tableting.
[0007] As an optimization, the modified bagasse is prepared by reacting bagasse pretreated with vinyltrimethoxysilane with bis(4-chlorophenyl)phosphine oxide, then with 2,4,6-triethylbenzene-1,3,5-trimethylamine, and then with bis(4-chlorophenyl)phosphine oxide to obtain phosphorus-containing bagasse, and the phosphorus-containing bagasse is reacted with 1,4-diamino-2,5-divinylbenzene, and then with terephthalaldehyde and p-phenylenediamine.
[0008] A method for preparing a doped and modified porous carbon negative electrode material comprises the following preparation steps:
[0009] (1) Pretreated bagasse, bis(4-chlorophenyl)phosphine oxide, Custer catalyst, and N,N-dimethylformamide are mixed in a mass ratio of 1:(0.5-0.7):(0.001-0.003):(20-30), heated to 100-120° C. and reacted for 20-22 hours. After the reaction is completed, the mixture is filtered and redispersed in N,N-dimethylformamide with a mass of 20-30 times that of the pretreated bagasse, 2,4,6-triethylbenzene-1,3,5-trimethylamine, sodium hydroxide, and tetrabutylammonium bromide are added, and stirred at 15-20° C. for 4-6 hours. Then, bis(4-chlorophenyl)phosphine oxide with a mass of 1.8-2.0 times that of the pretreated bagasse is added, and the mixture is heated to 25-30° C. and reacted for 4-6 hours. After the reaction is completed, the mixture is filtered and washed with pure water for 5 times, and dried at 80° C. for 24 hours to obtain phosphorus-containing bagasse;
[0010] (2) mixing phosphorus-containing bagasse, Custer catalyst, 1,4-diamino-2,5-divinylbenzene and N,N-dimethylformamide in a mass ratio of 1:(0.001-0.003):(2-3):(20-30), heating to 100-120° C. and reacting for 20-22 hours. After the reaction is completed, filtering and redispersing in toluene 20-30 times the mass of the pretreated bagasse, adding terephthalaldehyde 1.5-1.8 times the mass of the phosphorus-containing bagasse and p-phenylenediamine 1.5-1.8 times the mass of the phosphorus-containing bagasse under nitrogen protection, heating to 110-120° C. and reflux stirring for 2-3 hours, filtering and washing with ethanol 3-4 times, and drying at 80° C. for 24 hours to obtain modified bagasse;
[0011] (3) The modified bagasse and 10 wt% ferrous acetate solution are mixed in a mass ratio of 1:(10-12), stirred at room temperature for 22-24 hours, filtered and redispersed in a polydimethylsiloxane solution 10-12 times the mass of the modified bagasse, stirred for 5-10 minutes, filtered after the stirring, calcined in an argon tube furnace using a programmed calcination method, and ground through a 100 mesh sieve to obtain a modified negative electrode material;
[0012] (4) The modified negative electrode material, the conductive agent, and the binder are prepared into a negative electrode sheet by a pressing method in a mass ratio of 8:1:1 to obtain a doped modified porous carbon negative electrode material.
[0013] As an optimization, the preparation method of the pretreated bagasse in step (1) is: drying the bagasse at 80°C for 6 hours, crushing it with a high-speed crusher, passing it through a 100-mesh sieve, mixing the sieved bagasse and a 6% vinyltrimethoxysilane-acetone solution in a mass ratio of 1:20 for 4 hours, filtering and washing it with pure water for 5 times, and drying it at 80°C for 24 hours to obtain the pretreated bagasse.
[0014] As an optimization, the mass ratio of the pretreated bagasse, 2,4,6-triethylbenzene-1,3,5-trimethylamine, sodium hydroxide and tetrabutylammonium bromide in step (1) is 1:(0.8-1.0):(0.3-0.5):(0.4-0.6).
[0015] As an optimization, the Custer catalyst in step (2) and step (3) is di(1,3-divinyl-1,1,3,3-tetramethyldisiloxane)platinum.
[0016] As an optimization, the programmed calcination method in step (3) is to increase the temperature to 350°C at a rate of 3°C / min and keep it for 1 hour, then increase the temperature to 800°C at a rate of 5°C / min and keep it for 2 hours, and then cool to room temperature.
[0017] As an optimization, the polydimethylsiloxane solution is obtained by mixing polydimethylsiloxane and n-hexane in a mass ratio of 1:10. The model of polydimethylsiloxane is DC184, which is purchased from Dow Corning.
[0018] As an optimization, the conductive agent is acetylene black and the adhesive is polyvinylidene fluoride.
[0019] As an optimization, the preparation method of the negative electrode sheet is as follows: the binder and N-methylpyrrolidone are mixed in a mass ratio of 1:20, ultrasonically dispersed for 2 hours, and allowed to stand in a drying dish for 7 days to obtain a binder solution; the modified negative electrode material, the conductive agent, and the binder solution are mixed, and then 0.15 times the mass of the modified negative electrode material is added with N-methylpyrrolidone, and stirred for 1 hour under sealing conditions to obtain a slurry; the copper foil is fixed on a glass plate, and the slurry is coated on the copper foil with a coating thickness of 150 μm, and then placed in a 105°C vacuum drying oven for drying for 10 hours, and cut into pole pieces with a diameter of 6 mm with a slicer, and a powder tablet press is used to press the negative electrode sheet.
[0020] Compared with the prior art, the beneficial effects achieved by the present invention are:
[0021] When preparing the doped modified porous carbon negative electrode material, the present invention firstly reacts bagasse pretreated with vinyltrimethoxysilane with bis(4-chlorophenyl)phosphine oxide, then reacts with 2,4,6-triethylbenzene-1,3,5-trimethylamine, and then reacts with bis(4-chlorophenyl)phosphine oxide to obtain phosphorus-containing bagasse; secondly, the phosphorus-containing bagasse reacts with 1,4-diamino-2,5-divinylbenzene, and then reacts with terephthalaldehyde and p-phenylenediamine to obtain modified bagasse; the modified bagasse and ferrous acetate are mixed, and then mixed with polydimethylsilane, and dried, calcined, ground and pressed into tablets to obtain the modified porous carbon negative electrode material.
[0022] First of all, as a biomass waste, sugarcane bagasse is low-cost and widely available. It has a loose structure, a hollow vascular bundle shape, a smooth surface, and a small amount of pore structure. It provides a basis for the preparation of porous carbon materials. The sugarcane bagasse pretreated with vinyl trimethoxysilane contains abundant double bonds, which can react with bis(4-chlorophenyl)phosphine oxide under the action of a catalyst to make the sugarcane bagasse carry phosphorus and chlorophenyl. Then, it reacts with 2,4,6-triethylbenzene-1,3,5-trimethylamine and bis(4-chlorophenyl)phosphine oxide to obtain phosphorus-containing sugarcane bagasse. The phosphorus-containing sugarcane bagasse contains not only phosphorus and nitrogen, but also 2,4,6-triethylbenzene-1,3,5-trimethylamine and bis(4-chlorophenyl)phosphine oxide. The molecular cage structure obtained by the reaction of phosphine oxide with 1-(2-nitrogen)-2-nitrogen; the molecular cage structure will form a porous structure on the surface during the subsequent calcination and carbonization process, thereby increasing the specific surface area of the material; taking lithium-ion batteries as an example, doping atoms can improve the conductivity of the carbon negative electrode, expand the interlayer spacing and increase defect sites, thereby improving the electrode kinetics. Nitrogen is one of the most important doping elements of carbon materials. The electron donor performance of phosphorus atoms will affect the local charge density of the carbon matrix, provide free charge carriers, and facilitate the rapid migration of electrons. Phosphorus atoms will combine with the dangling bonds of carbon materials to form CP bonds. The larger atomic radius can expand the carbon layer spacing and introduce topological defects. These defects will create new active sites and enhance the contact characteristics with the electrolyte.
[0023] Secondly, after the phosphorus-containing sugarcane bagasse and 1,4-diamino-2,5-divinylbenzene are reacted, the sugarcane bagasse is again subjected to the action of a catalyst to allow the diphenylamine structure to be present. Through the subsequent Schiff base reaction with terephthalaldehyde and p-phenylenediamine, a polymer containing a Schiff base is generated on the sugarcane bagasse. The Schiff base polymer on the sugarcane bagasse has a complexing effect on metal ions. When the modified sugarcane bagasse and ferrous acetate are mixed, ferrous ions can be more evenly distributed on the sugarcane bagasse. During the subsequent calcination process, iron oxide is generated, which can undergo a reversible redox reaction with metallic lithium. Then, energy is stored by means of a large amount of electron transfer during the reaction, thereby improving the specific capacity.
[0024] Finally, the modified bagasse and ferrous acetate are mixed and then mixed with polydimethylsilane. The modified porous carbon negative electrode material is obtained by drying, calcining, grinding and pressing. The carbon material obtained after calcination is not only doped with nitrogen and phosphorus elements, but also contains iron oxide and silicon oxide. The synergistic effect of the above substances can further improve the electrical properties of the porous carbon negative electrode material. DETAILED DESCRIPTION
[0025] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0026] The Custer catalyst used in the following examples and comparative examples is di(1,3-divinyl-1,1,3,3-tetramethyldisiloxane) platinum; the polydimethylsiloxane solution used is obtained by mixing polydimethylsiloxane and n-hexane in a mass ratio of 1:10, the model of polydimethylsiloxane is DC184, purchased from Dow Corning; the conductive agent used is acetylene black; and the adhesive used is polytetrafluoroethylene.
[0027] Embodiment 1:
[0028] A method for preparing a doped and modified porous carbon negative electrode material, the method for preparing a doped and modified porous carbon negative electrode material comprising the following preparation steps:
[0029] (1) Dry the bagasse at 80°C for 6 hours, crush it with a high-speed crusher, pass it through a 100-mesh sieve, mix the sieved bagasse with a 6% vinyltrimethoxysilane-acetone solution at a mass ratio of 1:20 for 4 hours, filter it, wash it with pure water for 5 times, and dry it at 80°C for 24 hours to obtain pretreated bagasse; weigh the pretreated bagasse, 2,4,6-triethylbenzene-1,3,5-trimethylamine, sodium hydroxide, and tetrabutylammonium bromide at a mass ratio of 1:0.8:0.3:0.4; mix the pretreated bagasse, bis(4-chlorophenyl)phosphine oxide, Custer catalyst, N, N-dimethylformamide was mixed in a mass ratio of 1:0.5:0.001:20, heated to 120°C for reaction for 22 hours, filtered and redispersed in N,N-dimethylformamide with a mass of 20 times that of the pre-treated bagasse, 2,4,6-triethylbenzene-1,3,5-trimethylamine, sodium hydroxide, tetrabutylammonium bromide were added, stirred at 20°C for 6 hours, and then bis(4-chlorophenyl)phosphine oxide with a mass of 1.8 times that of the pre-treated bagasse was added, heated to 30°C for reaction for 6 hours, filtered and washed with pure water 5 times, and dried at 80°C for 24 hours to obtain phosphorus-containing bagasse;
[0030] (2) Phosphorus-containing bagasse, Custer catalyst, 1,4-diamino-2,5-divinylbenzene, and N,N-dimethylformamide were mixed in a mass ratio of 1:0.001:2:20, heated to 120°C for reaction for 22 hours, filtered and redispersed in toluene 20 times the mass of the pretreated bagasse after the reaction, and under nitrogen protection, 1.5 times the mass of terephthalaldehyde and 1.5 times the mass of p-phenylenediamine were added, heated to 120°C for 3 hours, filtered and washed with ethanol 4 times, and dried at 80°C for 24 hours to obtain modified bagasse;
[0031] (3) The modified bagasse and 10wt% ferrous acetate solution were mixed in a mass ratio of 1:10, stirred at room temperature for 24h, filtered and redispersed in a polydimethylsiloxane solution 10 times the mass of the modified bagasse, stirred for 10min, filtered after the stirring, and calcined in an argon tube furnace using a programmed calcination method, heating to 350°C at a rate of 3°C / min and keeping warm for 1h, then heating to 800°C at a rate of 5°C / min and keeping warm for 2h, then cooled to room temperature, and ground through a 100-mesh sieve after calcination to obtain a modified negative electrode material;
[0032] (4) Weigh the modified negative electrode material, conductive agent, and binder in a mass ratio of 8:1:1, mix the binder and N-methylpyrrolidone in a mass ratio of 1:20, disperse them by ultrasonication for 2 hours, and let them stand in a drying dish for 7 days to obtain a binder solution; mix the modified negative electrode material, conductive agent, and binder solution, add N-methylpyrrolidone in an amount of 0.15 times the mass of the modified negative electrode material, and stir for 1 hour under sealing conditions to obtain a slurry; fix a copper foil on a glass plate, coat the slurry on the copper foil with a coating thickness of 150 μm, and then place it in a vacuum drying oven at 105°C and dry it for 10 hours, cut it into electrode sheets with a diameter of 6 mm using a slicer, and press it into sheets using a powder tablet press to obtain a negative electrode sheet.
[0033] Embodiment 2:
[0034] A method for preparing a doped and modified porous carbon negative electrode material, the method for preparing a doped and modified porous carbon negative electrode material comprising the following preparation steps:
[0035] (1) Dry the bagasse at 80°C for 6 hours, crush it with a high-speed crusher, pass it through a 100-mesh sieve, mix the sieved bagasse and a 6% vinyltrimethoxysilane-acetone solution at a mass ratio of 1:20 for 4 hours, filter it, wash it with pure water for 5 times, and dry it at 80°C for 24 hours to obtain pretreated bagasse; weigh the pretreated bagasse, 2,4,6-triethylbenzene-1,3,5-trimethylamine, sodium hydroxide, and tetrabutylammonium bromide at a mass ratio of 1:0.9:0.4:0.5; mix the pretreated bagasse, bis(4-chlorophenyl)phosphine oxide, Custer catalyst, N, N-dimethylformamide was mixed in a mass ratio of 1:0.6:0.002:25, heated to 110°C for reaction for 21 hours, filtered and redispersed in N,N-dimethylformamide with a mass of 25 times that of the pretreated bagasse, 2,4,6-triethylbenzene-1,3,5-trimethylamine, sodium hydroxide, tetrabutylammonium bromide were added, stirred at 17°C for 5 hours, and then bis(4-chlorophenyl)phosphine oxide with a mass of 1.9 times that of the pretreated bagasse was added, heated to 27°C for reaction for 5 hours, filtered and washed with pure water 5 times, and dried at 80°C for 24 hours to obtain phosphorus-containing bagasse;
[0036] (2) Phosphorus-containing bagasse, Custer catalyst, 1,4-diamino-2,5-divinylbenzene, and N,N-dimethylformamide were mixed in a mass ratio of 1:0.002:2.5:25, heated to 110°C for reaction for 21 hours, filtered and redispersed in toluene 25 times the mass of the pretreated bagasse after the reaction, and under nitrogen protection, 1.6 times the mass of terephthalaldehyde and 1.7 times the mass of p-phenylenediamine were added, heated to 115°C for 2.5 hours, filtered and washed with ethanol three times, and dried at 80°C for 24 hours to obtain modified bagasse;
[0037] (3) The modified bagasse and 10wt% ferrous acetate solution were mixed in a mass ratio of 1:11, stirred at room temperature for 23h, filtered and redispersed in a polydimethylsiloxane solution 11 times the mass of the modified bagasse, stirred for 7min, filtered after the stirring, and calcined in an argon tube furnace using a programmed calcination method, heating to 350°C at a rate of 3°C / min and keeping warm for 1h, then heating to 800°C at a rate of 5°C / min and keeping warm for 2h, then cooled to room temperature, and ground through a 100-mesh sieve after calcination to obtain a modified negative electrode material;
[0038] (4) Weigh the modified negative electrode material, conductive agent, and binder in a mass ratio of 8:1:1, mix the binder and N-methylpyrrolidone in a mass ratio of 1:20, disperse them by ultrasonication for 2 hours, and let them stand in a drying dish for 7 days to obtain a binder solution; mix the modified negative electrode material, conductive agent, and binder solution, add N-methylpyrrolidone in an amount of 0.15 times the mass of the modified negative electrode material, and stir for 1 hour under sealing conditions to obtain a slurry; fix a copper foil on a glass plate, coat the slurry on the copper foil with a coating thickness of 150 μm, and then place it in a vacuum drying oven at 105°C and dry it for 10 hours, cut it into electrode sheets with a diameter of 6 mm using a slicer, and press it into sheets using a powder tablet press to obtain a negative electrode sheet.
[0039] Embodiment 3:
[0040] A method for preparing a doped and modified porous carbon negative electrode material, the method for preparing a doped and modified porous carbon negative electrode material comprising the following preparation steps:
[0041] (1) Dry the bagasse at 80°C for 6 hours, crush it with a high-speed crusher, pass it through a 100-mesh sieve, mix the sieved bagasse and a 6% vinyltrimethoxysilane-acetone solution at a mass ratio of 1:20 for 4 hours, filter it, wash it with pure water for 5 times, and dry it at 80°C for 24 hours to obtain pretreated bagasse; weigh the pretreated bagasse, 2,4,6-triethylbenzene-1,3,5-trimethylamine, sodium hydroxide, and tetrabutylammonium bromide at a mass ratio of 1:1.0:0.5:0.6; mix the pretreated bagasse, bis(4-chlorophenyl)phosphine oxide, Custer catalyst, N, N-dimethylformamide was mixed in a mass ratio of 1:0.7:0.003:30, heated to 100°C for reaction for 20 hours, filtered and redispersed in N,N-dimethylformamide with a mass of 30 times that of the pre-treated bagasse, 2,4,6-triethylbenzene-1,3,5-trimethylamine, sodium hydroxide, tetrabutylammonium bromide were added, stirred at 15°C for 4 hours, and then bis(4-chlorophenyl)phosphine oxide with a mass of 2.0 times that of the pre-treated bagasse was added, heated to 25°C for reaction for 4 hours, filtered and washed with pure water 5 times after the reaction, and dried at 80°C for 24 hours to obtain phosphorus-containing bagasse;
[0042] (2) Phosphorus-containing bagasse, Custer catalyst, 1,4-diamino-2,5-divinylbenzene, and N,N-dimethylformamide were mixed in a mass ratio of 1:0.003:3:30, heated to 100°C for reaction for 20 hours, filtered and redispersed in toluene 30 times the mass of the pretreated bagasse after the reaction, and under nitrogen protection, 1.8 times the mass of terephthalaldehyde and 1.8 times the mass of p-phenylenediamine were added to the bagasse, heated to 110°C, refluxed and stirred for 2 hours, filtered and washed with ethanol three times, and dried at 80°C for 24 hours to obtain modified bagasse;
[0043] (3) The modified bagasse and 10wt% ferrous acetate solution were mixed in a mass ratio of 1:12, stirred at room temperature for 22h, filtered and redispersed in a polydimethylsiloxane solution 12 times the mass of the modified bagasse, stirred for 5min, filtered after the stirring, and calcined in an argon tube furnace using a programmed calcination method, heating to 350°C at a rate of 3°C / min and keeping warm for 1h, then heating to 800°C at a rate of 5°C / min and keeping warm for 2h, then cooled to room temperature, and ground through a 100-mesh sieve after calcination to obtain a modified negative electrode material;
[0044] (4) Weigh the modified negative electrode material, conductive agent, and binder in a mass ratio of 8:1:1, mix the binder and N-methylpyrrolidone in a mass ratio of 1:20, disperse them by ultrasonication for 2 hours, and let them stand in a drying dish for 7 days to obtain a binder solution; mix the modified negative electrode material, conductive agent, and binder solution, add N-methylpyrrolidone in an amount of 0.15 times the mass of the modified negative electrode material, and stir for 1 hour under sealing conditions to obtain a slurry; fix a copper foil on a glass plate, coat the slurry on the copper foil with a coating thickness of 150 μm, and then place it in a vacuum drying oven at 105°C and dry it for 10 hours, cut it into electrode sheets with a diameter of 6 mm using a slicer, and press it into sheets using a powder tablet press to obtain a negative electrode sheet.
[0045] Comparative Example 1:
[0046] The preparation method of the doped modified porous carbon negative electrode material of Comparative Example 1 differs from that of Example 2 in that step (2) is not included, and step (1) is modified as follows: the bagasse is dried at 80°C for 6 hours, crushed with a high-speed crusher, and sieved through a 100-mesh sieve, and the sieved bagasse and a 6% vinyltrimethoxysilane-acetone solution are mixed in a mass ratio of 1:20 for 4 hours, filtered and washed with pure water 5 times, and dried at 80°C for 24 hours to obtain modified bagasse.
[0047] Comparative Example 2:
[0048] The preparation method of the doped modified porous carbon negative electrode material of Comparative Example 2 is different from that of Example 2 in that step (2) is not included, and step (1) is modified as follows: the bagasse is dried at 80°C for 6 hours, and then crushed with a high-speed crusher, and passed through a 100-mesh sieve, and the sieved bagasse and a 6% vinyltrimethoxysilane-acetone solution are mixed at a mass ratio of 1:20 for 4 hours, filtered and washed with pure water 5 times, and dried at 80°C for 24 hours to obtain pretreated bagasse; pretreated bagasse, 2,4,6-triethylbenzene-1,3,5-trimethylamine, sodium hydroxide, and tetrabutylammonium bromide are weighed at a mass ratio of 1:0.9:0.4:0.5; the pretreated bagasse is mixed with ... Bagasse, bis(4-chlorophenyl)phosphine oxide, Custer catalyst and N,N-dimethylformamide were mixed in a mass ratio of 1:0.6:0.002:25, heated to 110°C for reaction for 21 hours, filtered and redispersed in N,N-dimethylformamide with a mass 25 times that of the pretreated bagasse, added with 2,4,6-triethylbenzene-1,3,5-trimethylamine, sodium hydroxide and tetrabutylammonium bromide, stirred at 17°C for 5 hours, and then added with bis(4-chlorophenyl)phosphine oxide with a mass 1.9 times that of the pretreated bagasse, heated to 27°C for reaction for 5 hours, filtered and washed with pure water 5 times, and dried at 80°C for 24 hours to obtain modified bagasse.
[0049] Test Example 1:
[0050] Button cell assembly: the doped modified porous negative electrode material was vacuum dried at 105°C for 10 h and then placed in a vacuum glove box for assembly of button cells, wherein the metal lithium sheet was used as the electrode, the electrolyte was a mixture of 1 mol / L LiPF6 dimethyl carbonate (DMC), diethyl carbonate (DEC), and ethylene carbonate (EC) in a mass ratio of 2:2:1, the diaphragm was a Celgard 2400 porous polypropylene membrane, and the battery shell model was CR2025. Finally, the assembled button cell was sealed on a sealing machine with the positive electrode facing up and left to stand for 24 h to allow the electrolyte to fully contact the electrode before the electrochemical performance was tested.
[0051] Battery performance test:
[0052] Test method: The capacity and cycle performance of the battery were tested using Shenzhen Xinweier BTS-5V / 2.2A battery performance tester. The test voltage range was 0.01-2.0V, the material cycle performance current density was 100mA / g, one discharge and one charge was counted as one cycle, the battery discharge capacity at the 100th cycle was recorded, and the capacity retention rate was calculated. The results are shown in Table 1 below.
[0053] Table 1
[0054]
[0055]
[0056] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 2 in Table 1, it can be found that the doped modified porous carbon negative electrode material prepared by the present invention has good electrical properties.
[0057] By comparison, the electrical properties of Examples 1 to 3 are better than those of Comparative Examples 1 to 2, indicating that, firstly, the bagasse pretreated with vinyltrimethoxysilane contains abundant double bonds, which can react with bis(4-chlorophenyl)phosphine oxide under the action of a catalyst to make the bagasse carry phosphorus and chlorophenyl groups, and then react with 2,4,6-triethylbenzene-1,3,5-trimethylamine, and then react with bis(4-chlorophenyl)phosphine oxide to obtain phosphorus-containing bagasse. The phosphorus-containing bagasse contains not only phosphorus and nitrogen elements, but also a molecular cage structure obtained by reacting 2,4,6-triethylbenzene-1,3,5-trimethylamine with bis(4-chlorophenyl)phosphine oxide; During the subsequent calcination and carbonization process, the cage structure will form a porous structure on the surface, increasing the specific surface area of the material. Taking lithium-ion batteries as an example, doping atoms can improve the conductivity of the carbon negative electrode, expand the interlayer spacing and increase defect sites, thereby improving the electrode kinetics. Nitrogen is one of the most important doping elements in carbon materials. The electron donor performance of phosphorus atoms will affect the local charge density of the carbon matrix, provide free charge carriers, and facilitate the rapid migration of electrons. Phosphorus atoms will combine with the dangling bonds of carbon materials to form CP bonds. The larger atomic radius can expand the carbon layer spacing and introduce topological defects. These defects will create new active sites and enhance the contact characteristics with the electrolyte.
[0058] Secondly, after the phosphorus-containing bagasse and 1,4-diamino-2,5-divinylbenzene are reacted, the diphenylamine structure is allowed to remain on the bagasse through the action of a catalyst again, and a polymer containing a Schiff base is generated on the bagasse through a subsequent Schiff base reaction with terephthalaldehyde and p-phenylenediamine; the Schiff base polymer on the bagasse has a chelating effect on metal ions, and when the modified bagasse and ferrous acetate are mixed, ferrous ions can be more and more evenly distributed on the bagasse, and iron oxide is generated during the subsequent calcination process, which can undergo a reversible redox reaction with metallic lithium, and then a large amount of electron transfer during the reaction is used to store energy, thereby improving the specific capacity.
[0059] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations within the meaning and scope of the equivalent elements of the claims be included in the invention. Any marking in a claim should not be considered as limiting the claim to which it relates.
Claims
1. A doped and modified porous carbon negative electrode material, characterized in that: The doped modified porous carbon negative electrode material is obtained by mixing modified bagasse and ferrous acetate, and then mixing with polydimethylsilane, and then drying, calcining, grinding and tableting. The modified bagasse is prepared by reacting bagasse pretreated with vinyltrimethoxysilane with bis(4-chlorophenyl)phosphine oxide, then with 2,4,6-triethylbenzene-1,3,5-trimethylamine, and then with bis(4-chlorophenyl)phosphine oxide to obtain phosphorus-containing bagasse, and reacting the phosphorus-containing bagasse with 1,4-diamino-2,5-divinylbenzene, and then with terephthalaldehyde and p-phenylenediamine.
2. A method for preparing a doped and modified porous carbon negative electrode material, characterized in that: The method comprises the following preparation steps: (1) Pretreated bagasse, bis(4-chlorophenyl)phosphine oxide, Custer catalyst, and N,N-dimethylformamide are mixed in a mass ratio of 1:(0.5-0.7):(0.001-0.003):(20-30), heated to 100-120° C. and reacted for 20-22 hours. After the reaction is completed, the mixture is filtered and redispersed in N,N-dimethylformamide with a mass of 20-30 times that of the pretreated bagasse, 2,4,6-triethylbenzene-1,3,5-trimethylamine, sodium hydroxide, and tetrabutylammonium bromide are added, and stirred at 15-20° C. for 4-6 hours. Then, bis(4-chlorophenyl)phosphine oxide with a mass of 1.8-2.0 times that of the pretreated bagasse is added, and the mixture is heated to 25-30° C. and reacted for 4-6 hours. After the reaction is completed, the mixture is filtered and washed with pure water for 5 times, and dried at 80° C. for 24 hours to obtain phosphorus-containing bagasse; (2) mixing phosphorus-containing bagasse, Custer catalyst, 1,4-diamino-2,5-divinylbenzene and N,N-dimethylformamide in a mass ratio of 1:(0.001-0.003):(2-3):(20-30), heating to 100-120° C. and reacting for 20-22 hours. After the reaction is completed, filtering and redispersing in toluene 20-30 times the mass of the pretreated bagasse, adding terephthalaldehyde 1.5-1.8 times the mass of the phosphorus-containing bagasse and p-phenylenediamine 1.5-1.8 times the mass of the phosphorus-containing bagasse under nitrogen protection, heating to 110-120° C. and reflux stirring for 2-3 hours, filtering and washing with ethanol 3-4 times, and drying at 80° C. for 24 hours to obtain modified bagasse; (3) The modified bagasse and 10 wt% ferrous acetate solution are mixed in a mass ratio of 1:(10-12), stirred at room temperature for 22-24 hours, filtered and redispersed in a polydimethylsiloxane solution 10-12 times the mass of the modified bagasse, stirred for 5-10 minutes, filtered after the stirring, calcined in an argon tube furnace using a programmed calcination method, and ground through a 100 mesh sieve to obtain a modified negative electrode material; (4) The modified negative electrode material, the conductive agent, and the binder are prepared into a negative electrode sheet by a pressing method in a mass ratio of 8:1:1 to obtain a doped modified porous carbon negative electrode material.
3. The method for preparing a doped and modified porous carbon negative electrode material according to claim 2, characterized in that: The preparation method of the pretreated bagasse in step (1) is as follows: drying the bagasse at 80° C. for 6 hours, crushing it with a high-speed crusher, passing it through a 100-mesh sieve, mixing the sieved bagasse with a 6% vinyltrimethoxysilane-acetone solution at a mass ratio of 1:20 for 4 hours, filtering it, washing it with pure water for 5 times, and drying it at 80° C. for 24 hours to obtain the pretreated bagasse.
4. The method for preparing a doped and modified porous carbon negative electrode material according to claim 2, characterized in that: The mass ratio of the pretreated bagasse, 2,4,6-triethylbenzene-1,3,5-trimethylamine, sodium hydroxide and tetrabutylammonium bromide in step (1) is 1:(0.8-1.0):(0.3-0.5):(0.4-0.6).
5. The method for preparing a doped and modified porous carbon negative electrode material according to claim 2, characterized in that: The Custer catalyst in step (2) and step (3) is di(1,3-divinyl-1,1,3,3-tetramethyldisiloxane)platinum.
6. The method for preparing a doped and modified porous carbon negative electrode material according to claim 2, characterized in that: The programmed calcination method in step (3) is to increase the temperature to 350°C at a rate of 3°C / min and keep it for 1 hour, then increase the temperature to 800°C at a rate of 5°C / min and keep it for 2 hours, and then cool to room temperature.
7. The method for preparing a doped and modified porous carbon negative electrode material according to claim 2, characterized in that: The polydimethylsiloxane solution in step (3) is obtained by mixing polydimethylsiloxane and n-hexane in a mass ratio of 1:10, and the model of the polydimethylsiloxane is DC184.
8. The method for preparing a doped and modified porous carbon negative electrode material according to claim 2, characterized in that: In step (4), the conductive agent is acetylene black and the adhesive is polyvinylidene fluoride.
9. The method for preparing a doped and modified porous carbon negative electrode material according to claim 2, characterized in that: The preparation method of the negative electrode sheet in step (4) is as follows: a binder and N-methylpyrrolidone are mixed in a mass ratio of 1:20, ultrasonically dispersed for 2 hours, and allowed to stand in a drying dish for 7 days to obtain a binder solution; a modified negative electrode material, a conductive agent, and a binder solution are mixed, and then N-methylpyrrolidone in an amount of 0.15 times the mass of the modified negative electrode material is added, and stirred for 1 hour under sealing conditions to obtain a slurry; a copper foil is fixed on a glass plate, and the slurry is coated on the copper foil with a coating thickness of 150 μm, and then placed in a 105° C. vacuum drying oven for 10 hours, cut into electrode sheets with a diameter of 6 mm using a slicer, and press them with a powder tablet press to obtain a negative electrode sheet.
Citation Information
Patent Citations
Preparation method of silicon-carbon negative electrode
CN112768633A
Battery negative electrode material and preparation method thereof
CN113506865A
Nitrogen-phosphorus-chlorine co-doped carbon material, preparation method thereof and application of nitrogen-phosphorus-chlorine co-doped carbon material in lithium battery
CN114188537A
Nitrogen and phosphorus co-doped porous hard carbon material, preparation method and sodium ion battery
CN117985692A
Negative electrode active material, negative electrode, and method for manufacturing negative electrode active material
JP2018045996A